(3JGQjN GdMQjQjs - (3GHf GdMQjQj , CMeO Hf Ydj Hf GdeZQHj,J (B926 (3g` s
(3BNQgG (B:s
(3Je JGQjN GdMQjQi UGMH GdebGeGJ hgh NWC aGdcJGH dGHf GdMQjQi ceG CKHJfG s
(3GdfSNI eUhQI Yf fSNI GdaGJjcGfs
(3JGQjN jTed hjGJ eNJUQI ef SfI (B704(3Edi (B752s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B5s
Keywords: (3GdJGQjNs